(untitled) - Hogins, James Burl (Chicago, 1974)
Contents: Introduction: to the student; writing and rhetoric progtam; Objectives; Self-evaluation program; Answer key; Guide to usage and punctuation...
Keywords: English language,Ngôn ngữ Anh; Rhetoric,Hùng biện